A8.26 Bortezomib ameliorates the disease progression due to ovalbumin immunisation in NZB/W F1 lupus prone mice. (13th February 2015) - Khodadadi, L; Cheng, Q; Winter, O; Taddeo, A; Radbruch, A; Hoyer, BF; Hiepe, F
Abstract : Background and objectives: Plasma cell depletion with bortezomib can prevent the development of lupus nephritis and prolong survival in NZB/W mice. Here, we studied the effect of the immunisation with OVA in combination with bortezomib on the disease in NZB/W mice. Methods: NZB/W F1 female mice 16 week-old (early disease stage) were divided into 3 groups as follows: 1. Non-immunised mice as a control group, 2. Immunised mice; mice immunised with alum-precipitated OVA i.p and boosted 3 weeks after primary immunisation, 3. Immunised mice as group 2 receiving two shots of bortezomib (0.75 mg/kg, i.v) at 48 and 12 h before secondary immunisation. The numbers of anti-dsDNA antibody secreting cells (ASCs) were assessed in spleen and bone marrow by ELISPOT one month after secondary immunisation. Moreover we investigated serologic parameters including anti-OVA and anti-dsDNA antibody levels by ELISA as well as proteinuria and survival rate. Results: Immunised mice (group 2) developed proteinuria, which occurred earlier and stronger than in the non-immunised mice and in mice additionally treated with Bz before booster immunisation (group 3). Survival rate of immunised mice was reduced in comparison to group 3 treated with Bz while group 1 showed the longest survival. Autoantibody levels in group 2 and 3 were higher than in the control group 1. Mice immunised with OVA showed a tendency to higher numbers of IgM anti-dsDNA ASCs in the bone marrow and spleen than in non-immunised mice while IgG anti-dsDNA ASCs counts analysed in mice immunised with OVA and treated with Bz, were comparable with their counts in non-immunised mice. The Bz treatment before the secondary OVA immunisation resulted in lower anti-OVA antibody levels than in immunised mice without Bz treatment. Conclusion: Immunisation with alum-precipitated OVA accelerates autoimmunity in NZB/W mice. This effect can be ameliorated by plasma cell depletion with bortezomib.